Modeling the Total Energy Costs of Resistance Exercise: a Work in Progress - Victor M. Reis; Christopher B. Scott (Central European Journal of Sport Sciences and Medicine, 2016)
We present an aerobic and anaerobic, exercise and recovery energy cost model of intermittent energy costs utilizing task (work, Joules) as opposed to rate (per minute) measurements. Low to moderate intensity steady state exercise energy costs are typically portrayed as the volumetric rate at which oxygen is consumed (VO2 L min–1), where a proportionate upward climbing linear relationship is profiled with an increasing power output; add to this the concept of the anaerobic threshold and energy costs increase with more intense aerobic exercise in disproportion to VO2 L min–1 measurements. As a per task function, intermittent work and recovery bouts contain a combined estimate of total costs, that is as kJ or kcal (not kJ.min-1 or kcal.min-1). Adopting this approach to describe single and multiple sets of resistance training, the model that emerges for intermittent resistance exercise portrays linearity between equivalent work and total energy costs that differs proportionately among conditions – “continuous” muscular endurance vs. Intermittent higher load strength work, moderately paced vs. slower and faster conditions, smaller vs. larger working muscle masses and failure (fatigue) vs. non-failure states. Moreover, per kcal (or kJ) of total energy costs, work (J) is more inefficient with a greater load and lower repetition number as opposed to lower resistance with an increased number of repetitions. The concept of energy costs Rusing disproportionately with increased or prolonged work does not appear to apply to resistance exercise.